SODIUM REABSORPTION ESTIMATION FOR EVALUATION OF FUNCTIONAL STATE OF TRANSPLANTED KIDNEY - I. E. Borodoulin; I. A. Pronchenko; I. P. Ermakova (Вестник трансплантологии и искусственных органов)
Sodium reabsorption and sodium consumption (daily sodium excretion) were studied in 63 health volunteers and 100 recipients of kidney allografts. We elaborated the nomogramm for definition of sodium reabsorption with confidence interval 95% and proposed to use T-score CNa/GFR for a quantitative estimation of sodium reabsorption. There was a direct line dependence between sodium fractional excretion (CNa/GFR) and T-score CNa/GFR in kidney allograft recipients with good function and chronic rejection of kidney allograft (R = 0,86; р < 0,01; Yx = 0,593 + 0,64x; R = 0,97; р < 0,01; Yx = 0,147 + 1,146х and R = 0,97; р < 0,01; Yx = 0,21 + 0,69х, respectively). In recipients with good function of kidney allograft the regression coefficient was significantly higher, than in health volunteers (р < 0,01). In the group of recipients with chronic transplant rejection a free member of regression equation was significantly higher, than in health volunteers (р < 0,01). Consequently, exactness of sodium reabsorption estimation after kidney transplantation is not sufficient without calculation of sodium consumption.